2011
DOI: 10.1109/jsen.2011.2145369
|View full text |Cite
|
Sign up to set email alerts
|

Fastest Distributed Consensus Problem on Fusion of Two Star Sensor Networks

Abstract: Finding optimal weights for the problem of Fastest Distributed Consensus on networks with different topologies has been an active area of research for a number of years. Here in this work we present an analytical solution for the problem of Fastest Distributed Consensus for a network formed from fusion of two different symmetric star networks or in other words a network consists of two different symmetric star networks which share the same central node. The solution procedure consists of stratification of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…For ≤ 1 2 (wherẽ≥ ), we have 2 (W Q , ) ≥ 2 (W Q ,̃). Thus, the SDP formulation of (39) for N ≥ d 2 + 1 and 0 < ≤ 1 2 can be written as (40). For 1 2 ≤ < 1 (wherẽ≤ ), we have 2 (W Q , ) ≤ 2 (W Q ,̃).…”
Section: Quantum Gossip Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…For ≤ 1 2 (wherẽ≥ ), we have 2 (W Q , ) ≥ 2 (W Q ,̃). Thus, the SDP formulation of (39) for N ≥ d 2 + 1 and 0 < ≤ 1 2 can be written as (40). For 1 2 ≤ < 1 (wherẽ≤ ), we have 2 (W Q , ) ≤ 2 (W Q ,̃).…”
Section: Quantum Gossip Algorithmmentioning
confidence: 99%
“…The optimization problem (40) and (41) are similar to the fastest continuous-time quantum consensus problem. 28 For both cases of N ≤ d 2 and N ≥ d 2 + 1, as is approaching toward 1 2 (in either directions), the value of optimal convergence rate obtained from (40) and (41), respectively, is getting smaller (ie, faster convergence), where, for = 1 2 , all optimal convergence rates obtained from (40) and (41) are equal. Thus, it can be concluded that the optimal convergence rate as a function of reaches its optimal value for = 1 2 .…”
Section: Quantum Gossip Algorithmmentioning
confidence: 99%
See 3 more Smart Citations